Effect of Lecture and Group Discussion on Improving the Nutritional knowledge of Pregnant Women in Gorgan - Soheila Esfahankalate; Seyedeh Maryam Hasheminsab; Azam Esfahankalate (Golestan University of Medical Sciences, 2014)
Background and Objective: It is imperative that the application of appropriate educational methods is of paramount importance to nutrition knowledge and health of pregnant women. Hence, this study aimed at investigating the effect of lecture and group discussion on improving pregnant women's awareness. Material and Methods: This peri-experimental study was conducted on 110 pregnant women selected via cluster random sampling in eight villages of Gorgan, Iran, in 2009. They were allocated to two groups of lecture (n=52) and group discussion (n=36). The instrument was researcher made awareness questionnaire, consisting of 22 questions, whose reliability was confirmed by Alpha Cronbach (0.647) for data analysis, we used Pearson correlation, pared t test and t-dependent. Results: The mean age of lecture group was 24.65± 5.13 and that of group discussion was 23.56± 14.48. the educational level in 86.5% of lecture group and 94.4% of group discussion was at the level of middle school. There was no significant relationship between lecture group and group discussion. Furthermore , both groups had not any significant correlation with variables such as gestational age, pregnancy history and education level.Conclusion: Given that the current training programs in health system are adequate, it is a necessity to motivate and promote healthy behavior in pregnant women.